1980
DOI: 10.1037/0096-1523.6.4.751
|View full text |Cite
|
Sign up to set email alerts
|

Optic array determinants of apparent distance and size in pictures.

Abstract: This study explored whether special mechanisms are operative in picture perception to correct for the distortion that occurs when pictures are viewed from the wrong station point. Five photographs were taken of a layout composed of two same-sized dolls positioned at different distances on a flat untextured ground. Perspective differences existed between the photographs as a function of varying the distance of the camera to the layout. Each picture was viewed from five station points along the normal by 12 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Similarly, Farber and Rosinski (1978) found that when pictures of objects that were separated in depth (sagittally) were viewed from twice the correct viewing distance, their perceived separation in depth was twice as large, as compared with the canonical viewing position. Likewise, Bengston et al (1980) found that viewing photographs from incorrectly large distances increased judged pictorial depth. They had observers judge depth in photographs viewed from the wrong distance-that is, too far away from the distance that would be necessary to create an optic array roughly equivalent to what an observer would see if positioned at the lens of the camera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Farber and Rosinski (1978) found that when pictures of objects that were separated in depth (sagittally) were viewed from twice the correct viewing distance, their perceived separation in depth was twice as large, as compared with the canonical viewing position. Likewise, Bengston et al (1980) found that viewing photographs from incorrectly large distances increased judged pictorial depth. They had observers judge depth in photographs viewed from the wrong distance-that is, too far away from the distance that would be necessary to create an optic array roughly equivalent to what an observer would see if positioned at the lens of the camera.…”
Section: Discussionmentioning
confidence: 99%
“…To mention a few, there is an amazing robustness of pictorial space, despite sometimes dramatic projective distortion (Pirenne, 1970). It is not settled whether this robustness is best interpreted as an array-specific extraction of depth information (Bengston, Stergios, Ward, & Jester, 1980;Gibson, 1954), as a lack of discriminability, or as the result of an effective compensation mechanism (Cutting, 1987). Also, the ability to compensate is highly dependent on viewing conditions, such as vantage point.…”
Section: Pictorial Effects On Perceived Visual Spacementioning
confidence: 99%
“…These manipulations affect perceived virtual layout despite the visibility of the picture surface (Kraft & Green, 1989). Similarly, varying the observer's viewing distance to a picture changes egocentric and exocentric depth estimates but not estimates of object width and size (Bengston, Stergios, Ward, & Jester, 1980;O. W Smith, 1958aO.…”
mentioning
confidence: 99%
“…When one is closer to a photograph, for example, than the focal length of the lens times the magnification, apparent depth should be compressed; when one is farther away, it should expand; and, most interestingly, when one is off to one side, it should undergo affine shear. Haber (1978Haber ( , 1983, Hagen (1974), Hochberg (1986), and Sedgwick (1986) have discussed these issues; Bengston et al (1980), Ellis, Smith, and McGreevy (1987), Goldstein (1979Goldstein ( , 1987, Halloran (1989), Kraft and Green (1989), , and Rosinski, Mulholland, Degelman, and Farber (1980) have provided data showing effects of affine shears and compressions in pictorial space; and Cutting (1986aand Cutting ( , 1987and Cutting ( , 1989, Farber and Rosinski (1978), and, most notably, Kubovy (1986) and Pirenne (1970) have provided analyses of spatial distortions consistent with those of La Gournerie.…”
mentioning
confidence: 99%
“…Viewpoint-independent utility is theoretically surprising because the geometric layout of virtual space "behind" the picture surface is correct only for one viewpoint, variously called the station point (Bengston, Stergios, Ward, & Jester, 1980;Cutting, 1986a;Gibson, 1979;Haber, 1978), the center a/projection (Farber & Rosinski, 1978;Kubovy, 1986), or the composition point (Cutting, 1988). (The line to this point from the center of the picture is called the principal ray, to which we will refer later.)…”
mentioning
confidence: 99%